El impuesto a la salida de divisas presuntivo y el efecto financiero en las compañías exportadoras del sector bananero - Mayorga López, Ayli Aránzazu (2021)
The purpose of this research is to present the results of the financial effects that the Presumptive Foreign Exchange Outflow Tax has had on banana exporting companies. Therefore, three impact scenarios were considered: No provision is made for the Presumptive Foreign Exchange Outflow Tax on exports, the tax is considered as a deductible expense (i.e. provisioned) and assumed as a non-deductible expense. The methods and procedures applied were: financial and tax analysis. It is concluded that this tax has a strong impact on all companies involved in the export of goods or services, because they must ensure that the collection management they carry out with their clients abroad is effective, so that their payments are returned to the country within 6 months to avoid a presumptive payment that may not correspond to the exact value to be paid.............